Kelimpahan Ikan Clownfish (Amphiprioninae Ocellaris) Sebagai Bioindikator Kondisi Karang Di Gili Labak, Madura - Yunita Vernandha; Nirmalasari Idha Wijaya; Nor Sa'adah (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2022)
Coral reefs are a habitat for more than 300 types of coral, 200 species of fish, and various other invertebrates such as molluscs, crustaceans, sponges, algae, and other biotas. Sea anemones are sea animals from the Anthozoa taxonomic class, which are flower-shaped. Clownfish have an attractiveness with its the color which has a basic color pattern with a combination: red - white, red - black and black - yellow - white. The purpose of this research is to analyze the condition of the corals and the abundance of clownfish on Gili Labak Island, Sumenep. This research was conducted in October 2021 on Gili Labak Island, Sumenep. The method used to collect data on the condition of coral reefs is using a belt transect with a length of 50 m parallel to the shoreline to collect data on the abundance of clownfish using the UVC (underwater visual census) method and to collect data on brightness, salinity, temperature and current velocity using in situ data (direct). The results obtained from this research is the relationship between coral reef conditions and clownfish, namely a positive correlation with a coefficient of determination (R²) = 0.8048. The relationship between coral reef conditions and sea anemone abundance is a negative correlation with the coefficient of determination (R²) = 0.2049.